Zakat Management: Update-To-Down Zakat Governance in the Amil Zakat Agencies in Indonesia, Malaysia and Brunei Darussalam - Imam Gracia Marshall; Sri Herianingrum (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2021)
Islam invites, recommends and obliges all of its people to do zakat, infaq, alms and waqf (ZISWAF) as an effort to provide a sense of justice and equality among humans in order to increase gratitude to ﷲ. One of the efforts is by means of zakat, how is a mu'min who has reached the nisab of zakat to give zakat. With the current condition of Indonesia, which already has Baznas (National Zakat Agency) and many Amil Zakat Institutions (LAZ) which are managed by various types of communities, organizations, institutions and institutions, it should decrease the poverty value and increase the level of welfare every year. But the reality is the opposite. The Central Statistics Agency (BPS) released data on the number of poor people in March 2020 amounting to 26.42 million people, even though Indonesia's Muslim population is approximately 220 million people who should have good and healthy management and management to reduce the number of poor people in Indonesia in order to increase welfare of Indonesia. Even good governance is the main key in increasing welfare in Indonesia.Keywords: Zakat, Baznas, Poverty, Welfare, Zakat Management